Enhancing the Performance of Subband Audio Coders for Speech Signals - Malvar, Henrique S. (International Symposium on Circuits and Systems, 1998)
Transform or subband audio coders can deliver high quality reconstruction at rates around two bits per sample. Most quantization strategies take into account masking properties of the human ear to amke the quantization noise less noticeable. In this paper we describe a new coder in which we extend such quantization strategies by incorporating run-length and arithmetic encoders. They lead to improved performance for quasi-periodic signals, including speech. The quantization tables are computed from only a few parameters, allowing for a high degree of adaptability without increasing quantization table storage. To improve the performance for transient signals, the coder uses a nonuniform modulated lapped biorthogonal transform with variable resolution without input window switching. Experimental results show that the coder can be used for good quality signal reproduction at rates close to one bit per sample, and quasi-transparent reproduction at two bits per sample.